2020
DOI: 10.1016/j.yebeh.2020.107372
|View full text |Cite
|
Sign up to set email alerts
|

Mapping epilepsy-specific patient-reported outcome measures for children to a proposed core outcome set for childhood epilepsy

Abstract: The objectives of the study were to (1) map questions in epilepsy-specific patient-reported outcome measures (PROMs) of children's health-related quality of life (HRQoL) to a proposed core outcome set (COS) for childhood epilepsy research and (2) gain insight into the acceptability of two leading candidate PROMs. Method: We identified 11 epilepsy-specific PROMs of children's HRQoL (17 questionnaire versions) in a previous systematic review. Each item from the PROMs was mapped to 38 discrete outcomes across 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Here, health status includes physical and mental health, as well as cognitive and behavioral functions that show problems, because diseases cause difficulties in an individual's daily life or role performance. In addition, individuals' unique inner resources such as self-esteem and self-efficacy are strongly related to HRQOL in children with epilepsy, and their presence plays an important buffer in attenuating the negative effects of factors that deteriorate HRQOL [3,25,[32][33][34][35][36][37][38][39].…”
Section: ) Organism: Intrapersonal Factors Of Children With Epilepsy ...mentioning
confidence: 99%
“…Here, health status includes physical and mental health, as well as cognitive and behavioral functions that show problems, because diseases cause difficulties in an individual's daily life or role performance. In addition, individuals' unique inner resources such as self-esteem and self-efficacy are strongly related to HRQOL in children with epilepsy, and their presence plays an important buffer in attenuating the negative effects of factors that deteriorate HRQOL [3,25,[32][33][34][35][36][37][38][39].…”
Section: ) Organism: Intrapersonal Factors Of Children With Epilepsy ...mentioning
confidence: 99%
“…Although this paper provides insights into current content validation methods it is not a comprehensive of all methods that can be used. For example, quantitative methods like content validity indices (6,10,68,70,77,78) (a survey method), concept/content mapping (62), mapping to consensus core sets (79), theoretical models other than ICF, clarification of conceptual models/construct definitions (80), or qualitative methods other than cognitive interviewing (69) were not explored in this paper. Given the array of appropriate methods that could be used in content validation, a prescriptive approach to content validation might lead to narrow thinking.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, researchers have used the Delphi technique to ask stakeholders, including families, to determine what issues they consider important enough to be included in PROMs. 18,20,42…”
Section: Approaches To Map Items and Domainsmentioning
confidence: 99%
“…To support comprehensive evidence‐based recommendations for selecting the most suitable PROM for a given purpose, the Consensus‐based Standards for the selection of Health Measurement INstruments (COSMIN) initiative developed methodological standards for studies by selecting a minimum core set of outcomes that should be measured and reported in all clinical trials of a specific condition or trial population 16 . Systematic reviews are available for many neurologically‐based conditions: muscular dystrophy, 48,49 autism spectrum disorder, 50 child disability, 51 epilepsy, 42,52 survivors of brain tumour and other acquired brain injuries, 53 and pediatric multiple sclerosis 54 . The Core Outcome Measures in Effectiveness Trials are seeking consensus on what is important and meaningful to measure and are available for antiepileptic therapy in pediatric epilepsy 55 .…”
Section: Qol‐related Measures For Young People With Neurological Impa...mentioning
confidence: 99%